2013
DOI: 10.1007/s00210-013-0846-3
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation of human pulmonary arteries by PPARγ agonists

Abstract: It has been suggested that activation of nuclear peroxisome proliferator-activated receptors γ (PPARγ) may represent a new strategy for the treatment of pulmonary arterial hypertension. It has been demonstrated that PPARγ activation relaxed the isolated mouse pulmonary artery. The aims of the present study were to examine whether and to which extent the two PPARγ agonists rosiglitazone and pioglitazone relax the isolated human pulmonary artery and to investigate the underlying mechanism(s). Isolated human pulm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 41 publications
3
12
0
Order By: Relevance
“…This study found that the PPARc antagonists pioglitazone and rosiglitazone act to relax human pulmonary arteries, and that rosiglitazone was the most potent vasodilator [82]. These results further suggest that PPARc antagonists may also be a novel therapeutic route for the treatment of PAH.…”
Section: Pparc Agonistssupporting
confidence: 53%
“…This study found that the PPARc antagonists pioglitazone and rosiglitazone act to relax human pulmonary arteries, and that rosiglitazone was the most potent vasodilator [82]. These results further suggest that PPARc antagonists may also be a novel therapeutic route for the treatment of PAH.…”
Section: Pparc Agonistssupporting
confidence: 53%
“…PPARγ activation is reported to increase blood flow via vasodilation [31, 42]. We examined vascular response to PPARγ in HS and NS-fed A 2A AR +/+ and A 2A AR −/− mice using selective PPARγ agonist, Rosiglitazone.…”
Section: Discussionmentioning
confidence: 99%
“…Thiazolidinedione (TZD), specific PPARγ ligands, has been reported to lower blood pressure and provide cardiovascular benefits through regulating vascular function and vascular tone [30]. Studies have demonstrated that PPARγ activation elicits relaxation in pulmonary arteries by activating K ATP channels through unknown mechanism [31]. …”
Section: Introductionmentioning
confidence: 99%
“…The use of rosiglitazone, a PPARgamma agonist, promoted pulmonary artery vasorelaxation in an in vitro study [12]. Another curious fact is the improvement of obese patients with PAH after undergoing bariatric surgery, which, in addition to inducing significant weight loss, also promotes an increase in incretin secretion, including GLP-1 [9].…”
Section: Discussionmentioning
confidence: 99%